Spontaneous Rapid Resolution of Traumatic Subarachnoid Hemorrhage - Kurve, Ajay; Mahapatra, A K (Indian Journal of Neurotrauma, 2005)
We report a 32-year-old male with severe head injury in whom traumatic subarachnoid hemorrhage resolved spontaneously. On admission, Glasgow Coma Score was 6/15 and CT scan revealed grade III subarachnoid hemorrhage with evidence of diffuse axonal injury and small hemorrhagic contusion in left temporal lobe. Patient improved with conservative management, and serial CT 24 hours later showed complete resolution of subarachnoid hemorrhage.
Keywords: diffuse axonal injury; head injury; subarachnoid hemorrhage